Utilising the Stone Age for sport historical teaching (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In this article the author explored sport history pedagogy by combining the Canadian Benchmarking Project with the Revised Bloom’s Taxonomy (RBT) for teaching ancient culture to undergraduate students of sport history. The article was introduced by presenting some common understanding of what constitutes the subject, sport history and explaining what pedagogical tools teachers can employ to counter the antagonism that students generally display towards the subject. It was argued that these tools are best utilised by identifying three domains of learning and teaching (cognitive, affective and physcomotor) in sport history. The researcher chose the Stone Age period as a topic of research and class presentation. Next, a narrative was created about this period, placing it within world context. Then the narrative was converted into pedagogical assessment experiences by using the RBT for use inside and outside the classroom but within the boundaries of the formal university sport history curriculum. Finally, the assessment experiences were summarised after a third year sport history class completed them.
Keywords: Bloom’s Revised Taxonomy; Canadian Benchmarking Project; Stone Age; Sport history; Stellenbosch